Improved performance of the microbial electrolysis desalination and chemical-production cell with enlarged anode and high applied voltages. (November 2017) - Ye, Bo; Luo, Haiping; Lu, Yaobin; Liu, Guangli; Zhang, Renduo; Li, Xiao
Graphical abstract: Highlights: The maximum current density in this study reached 32.8 ± 2.6 A/m 2 . MEDCC could maintain high performance under the applied voltage of 2.5 V. The relative abundance of Geobacter was changed along the anode length. Abstract: The aim of this study was to improve performance of the microbial electrolysis desalination and chemical-production cell (MEDCC) using enlarged anode and high applied voltages. MEDCCs with anode lengths of 9 and 48 cm (i.e., the 9 cm-anode MEDCC and 48 cm-anode MEDCC, respectively) were tested under different voltages (1.2–3.0 V). Our results demonstrated for the first time that the MEDCC could maintain high performance even under the applied voltage higher than that for water dissociation (i.e., 1.8 V). Under the applied voltage of 2.5 V, the maximum current density in the 48 cm-anode MEDCC reached 32.8 ± 2.6 A/m 2, which is one of the highest current densities reported so far in the bioelectrochemical system (BES). The relative abundance of Geobacter was changed along the anode length. Our results show the great potential of the BES with enlarged anode and high applied voltages.